Electrical and optical properties of dip coated Al-doped ZnO thin films : Effect of Al-concentration, starting solution and sample ageing - Yadav, Ram Phul; Rai, Krishna Bahadur; Shrestha, Shankar Prasad (Mongolian Journal of Chemistry, 2021)
Undoped and Aluminum doped Zinc Oxide thin films were synthesized by dip coating technique. The electrical properties of the films were studied due to the Aluminum doping, starting solution aging and sample aging. The sheet resistance of ZnO:Al films was minimum at 2.5 at % whereas carrier concentration is maximum. Both undoped and aluminum doped Zinc Oxide thin films were found to be highly transparent lying in between 65 - 79 % in the wavelength range 367 nm to 1038 nm. The band gap of deposited films changed slightly from 3.22 eV to 3.27 eV.